PENDUGAAN JARAK GENETIK, VARIABEL PEMBEDA BANGSA PADA KAMBING LOKAL MELALUI PENDEKATAN ANALISIS MORFOLOGI - Saparto Saparto (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2005)
The aim of this research was to estimate the genetic distance and discriminant variables between local goat breeds, and also to know the accuration of classifying of local goat breeds by morphological analysis. The number ofsamples examined for Etawah grade, Jawarandu, Kejobong, and Kacang goats were 10, 11, 7 and 14, respectively. Zoometrical variables studied were body weight, body length, wither height, chest circumference, chest depth, chest wide, hip height, hip depth, ear length, and tail length. The SAS ( 1990) was applied for discriminant and canonical analysis. Results showed that : (I) The smallest genetic distance was between the Kejobong goat and the Jawarandu goat and was 11,32; While the largest genetic distance was between the Etawah grade goat and the Kacang goat and was 313,95; (2) Results from distribution mapping produced by canonical analysis showed that almost all groups breed clearly separate, except partly Kejobong goat and Jawarandu goat close together; (3) Ear length and tail length were the best discriminator for the first canonical variate; and tail length, hip height and ear length were the best discriminator for the second one; (4) The higest similarity individual inside the group was obtained from Etawah grade, Jawarandu, and Kacang goat, and was I 00 %. The group Kejobong goat was mixed by J awarandu goat with 14,29 %; (5) Breeds resulted high accuracy as indicated by the low probability of errorneous discrimination. The accuracy accounted 96,43 %, the rate misclassification 3,57 %.